A yeast mitogen-activated protein kinase homolog (Mpk1p) mediates signalling by protein kinase C. - Lee, K S (1993)
Mitogen-activated protein (MAP) kinases are activated in response to a variety of stimuli through a protein kinase cascade that results in their phosphorylation on tyrosine and threonine residues. The molecular nature of this cascade is just beginning to emerge. Here we report the isolation of a Saccharomyces cerevisiae gene encoding a functional analog of mammalian MAP kinases, designated MPK1 (for MAP kinase). The MPK1 gene was isolated as a dosage-dependent suppressor of the cell lysis defect associated with deletion of the BCK1 gene. The BCK1 gene is also predicted to encode a protein kinase which has been proposed to function downstream of the protein kinase C isozyme encoded by PKC1. The MPK1 gene possesses a 1.5-kb uninterrupted open reading frame predicted to encode a 53-kDa protein. The predicted Mpk1 protein (Mpk1p) shares 48 to 50% sequence identity with Xenopus MAP kinase and with the yeast mating pheromone response pathway components, Fus3p and Kss1p. Deletion of MPK1 resulted in a temperature-dependent cell lysis defect that was virtually indistinguishable from that resulting from deletion of BCK1, suggesting that the protein kinases encoded by these genes function in a common pathway. Expression of Xenopus MAP kinase suppressed the defect associated with loss of MPK1 but not the mating-related defects associated with loss of FUS3 or KSS1, indicating functional conservation between the former two protein kinases. Mutation of the presumptive phosphorylated tyrosine and threonine residues of Mpk1p individually to phenylalanine and alanine, respectively, severely impaired Mpk1p function. Additional epistasis experiments, and the overall architectural similarity between the PKC1-mediated pathway and the pheromone response pathway, suggest that Pkc1p regulates a protein kinase cascade in which Bck1p activates a pair of protein kinases, designated Mkk1p and Mkk2p (for MAP kinase-kinase), which in turn activate Mpk1p.